Evaluation of psychological stress and its relationship to the skills of passing from the bottom and top in volleyball for fourth-year students in the College of Physical Education and Sport Sciences - Hikmet Fadil, Asmaa (International Journal of Psychosocial Rehabilitation, 2020)
The research aims: to evaluate the psychological pressure for students of the fourth stage in the Faculty of Physical Education and Sports Science , University of Baghdad for the year 2018-2019, as I use the descriptive survey style to fit in solving the problem of research, have been identified sample purposively, and represented the students of the fourth stage in the College of Education Physical education and sports sciences at the University of Baghdad, whose number is 84 male and female students distributed among 6 divisions by, 3 for male and 3 for female students, and the sample of the exploratory experiment included 18 students from outside the research sample. Since the scale was applied to 60 of the students, in order to determine the measure of the validity and find a scientific basis for the measure, we have extracted grading standards and levels on the main sample of 84 students; we reach the following conclusions: Evaluation of psychological stress , a discrepancy clear In students ’ levels, by comparing the standard scores achieved with the levels of normal distribution and determining the relationship between psychological pressure and the performance of the two passing skills from the top and the bottom, the recommendations were for the necessity of measuring psychological pressure to stand at the level of students’ psychological state and applying the scale to other games to determine the level of psychological stress.